2018
DOI: 10.3389/fimmu.2018.01003
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Helicobacter pylori Infection in BALB/c Mouse Model by Oral Administration of Multivalent Epitope-Based Vaccine of Cholera Toxin B Subunit-HUUC

Abstract: Vaccination is an increasingly important alternative approach to control Helicobacter pylori infection, since H. pylori resistance to previously efficacious antibiotic regimens is increased, and H. pylori eradication treatment for upper gastrointestinal diseases is becoming less successful. Fortunately, an efficient oral monovalent H. pylori vaccine has been developed. However, compared with monovalent vaccines, multivalent vaccines have the potential to induce more effective and comprehensive protection again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 47 publications
0
38
0
2
Order By: Relevance
“…Infection with H. pylori , which is characterized as highly pathogenic and difficult to eradicate, is the major cause of GC . However, the molecular mechanisms underlying H. pylori infection‐mediated GC are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with H. pylori , which is characterized as highly pathogenic and difficult to eradicate, is the major cause of GC . However, the molecular mechanisms underlying H. pylori infection‐mediated GC are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…33 Ghasemi et al 34 34 Moreover, vaccinated mice showed a mixed Th1/ Th2/Th17 response and antigen-specific IgG2a/IgG1 production. 35 Increased lymphocyte proliferation and IFNγ, interleukin-4 (IL-4), and interleukin-17 (IL-17) production were also observed in the CTB-HUUC-vaccinated animals. 34 No sign of toxicity was noted in the vaccinated mice.…”
Section: Selection Of Novel Protective Antigens and Epitopesmentioning
confidence: 99%
“…34 Another multivalent epitope-based vaccine (CTB-HUUC), comprising CTB adjuvant and tandem copies of B-and T-cell epitopes from H pylori adhesion A subunit (HpaA), urease A subunit (UreA), UreB, and CagA induced significant increased levels of H pylorispecific serum and mucosal antibody responses, when compared with mice immunized with CTB alone or PBS. 35 Increased lymphocyte proliferation and IFNγ, interleukin-4 (IL-4), and interleukin-17 (IL-17) production were also observed in the CTB-HUUC-vaccinated animals. Both oral prophylactic and therapeutic vaccination routes with CTB-HUUC provided significant protection, equivalent to approximately 4-and 2-log decreases in bacterial loads, respectively, against H pylori challenge in BALB/c mice.…”
Section: Selection Of Novel Protective Antigens and Epitopesmentioning
confidence: 99%
“…The most important reason for this observation must be that the RBD-TcdA/B vaccine can induce the production of more types and higher levels of RBD-specific antibodies, which can block two toxin RBDs to inhibit the action of the toxins. Moreover, toxins can be used as adjuvant in several research models [39,40]. In our study, we found that the anti-toxin A, but not anti-toxin B, neutralizing antibody titer induced by the RBD-TcdA/B vaccine was much higher than that induced by the single one.…”
Section: Discussionmentioning
confidence: 55%